Unexpected H₂ solubility of polyimide/polyphthalonitrile H₂-selective membranes with tailorable microstructure and performance - Hu, Chun Po (2023)
Membrane separation technologies are emerging as energy-efficient alternatives to traditional distillation processes. The growing demand for clean energy on “hydrogen economy” has highlighted the need for high-performance H2-selective gas separation membranes. Polyimides (PIs) show promise in these applications due to their excellent thermal stability, good hydrogen permeability, and processability. However, PIs often have insufficient selectivity, mainly because they have a poor affinity H2 over other gases. Despite the rigid molecular structure of polyimides provides excellent size-sieving property for hydrogen, the low H2 solubility of PIs limits the H2 selectivity, which is crucial for hydrogen purification. To address this issue, this study demonstrated a simple blending method to fabricate polyimide/polyphthalonitrile blend membranes with adjustable microstructure.